DESAIN DAN UJI COBA PRAKTIKUM GREEN CHEMISTRY DENGAN MEMANFAATKAN LOGAM BEKAS PADA SEL VOLTA - kuncoro hadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
ABSTRACT The design and testing of green chemistry practicum by utilizing scrap metal in voltaic cells has been carried out with the R&D approach. R&D research used with the 4 Stages of Research Implementation. Based on the results of the study obtained an average value of practical guidance in terms of material, media and teacher ratings respectively 4.76, 4.62, and 4.56. With the percentage values obtained respectively at 95.2%, 92.4%, and 94.8%. The results of the trial obtained ease in implementing the lab guide. Practicum guides can be used as a reference for students in practicum and can be used as a reference for teachers in guiding students. Keywords: green chemistry, scrap metal, voltaic cells, R&D research